Literature Review: Ice Cube Therapy to Reduce Thirst in Patients Undergoing Hemodialysis - Saputra, M. Rezza Januar; Sumardino, Sumardino; Rifai, Akhmad; Sugiyarto, Sugiyarto (Poltekkes Kemenkes Riau, 2023)
Chronic kidney failure is a malfunction of the kidneys which occurs over a relatively long period of time, this is the cause of reduced individual ability to maintain metabolism, fluid balance in the body which will then cause high urea values. Hemodialysis (HD) is an attempt to replace kidney function in filtering metabolic wastes, water and maintaining electrolyte levels in the body through a semi-shift membrane called Dalizer. . Ice Cubes therapy can help reduce thirst and freshen the throat. Ice cubes therapy is done by sucking ice cubes, where ice cubes can give a fresher feeling than drinking small amounts of mineral water, gargling with boiled water, gargling with medicines and others. To identify the effect of ice cube's on efforts to reduce thirst in patients undergoing hemodialysis. Data collection used the literature review study method using the Ebsco, Google Schooler, and Elsevier databases. With keywords: Ice Cube's Therapy, Hemodialysis Patients, Thirst with limited articles from 2018-2023. Obtained from 10 articles with 148 respondents in the Pretest Posttest research design and 4 respondents with a case study research design showing that there was an effect of ice cube's therapy on decreasing thirst in CKD patients undergoing Hemodialysis. In this literature review, it was found that there was an effect of ice cube's therapy on reducing thirst in CKD patients who were undergoing hemodialysis.